Antibiotic Resistance in Black Sea Microbial Communities - Prekrasna, Ievgeniia; Pavlovska, Mariia; Dzhulai, Artem; Dykyi, Evgen; Alygizakis, Nikiforos; Slobodnik, Jaroslav (Frontiers in Environmental Science, 2022)
Background. Antibiotic resistance genes (ARGs) are considered as pollutants and are found in natural and anthropogenically impacted environments. Distribution of ARGs in marine environment poses a threat to human health turning the water body into a pool for the ARGs’ transmission. Objectives. A large-scale study of antibiotic resistance in microbial communities has been performed in the Black Sea, both in the coastal and offshore regions. Methods. The quantitative distribution of the genes responsible for the inactivation of the beta-lactam (blaCMY, blaSHV), vancomycin (vanA, vanB), macrolides (ermB) and colistin (mcr-1) was assessed with real-time quantitative PCR. Concentrations of the antibiotics belonging to the classes of beta-lactam/cephalosporin/carbapenem, macrolides and glycopeptides were determined by LC-ESI-QTOF-MS. Results. The present study revealed the distribution of antibiotic resistance genes targeting the response to all antibiotics included in our analysis at various locations across the Black Sea. According to the ARGs copy number normalized to the 16S rRNA, vanB (2×10-1±1×10-1) and blaSHV (4×10-2±1×10-2) were the most numerous genes, followed by blaCMY (1×10-2±3×10-3) and mcr-1 (3×10-2±2×10-2). The less abundant gene was ermB (1×10-3±5×10-4) and vanA (1×10-5±5×10-4). The mcr-1, blaCMY and blaSHV had moderate positive correlation with markers of ruminant feacal pollution. The concentration of antibiotics in seawater was below the detection limit. The abundance of all ARGs included in the study was significantly higher (p-value<0.05) within the northwest coastal area when compared to the offshore stations. The results clearly indicate an alarming antibiotic resistance problem in the region and call for a regular monitoring of ARGs abundance in the Black Sea and its major freshwater tributaries.